Uji Mutu Pelet Kayu Durian (Durio zibethinus) dengan Perekat Tepung Tapioka: Quality Assessment of Durian Wood (Durio zibethinus) Pellets Using Tapioca Starch Binder - Lies Indrayanti; Alpian Alpian; Penyang Penyang; Chartina Pidjath; Wahyu Supriyati; William A (JURNAL HUTAN TROPIKA, 2026)
The quality of wood pellets produced from durian wood (Durio zibethinus) sawdust with tapioca starch as an adhesive was evaluated. The research was conducted at the Forest Product Technology Laboratory, Department of Forestry, and the Integrated Laboratory of the University of Palangka Raya, as well as at the Standardization and Industrial Services Center (BSPJI) Banjarbaru. Six quality parameters were analyzed based on the Indonesian National Standard (SNI) 8041:2014, and the results were compared with the French standard (ITEBE). A factorial Completely Randomized Design (CRD) was applied with two factors: wood part (stem, branch, twig) and adhesive proportion (7.5%, 10%, 12.5%). It was found that durian wood pellets met the SNI requirements for moisture content, volatile matter, ash content, and calorific value in six treatment combinations with values exceeding 4,000 cal g⁻¹. However, density, fixed carbon, and calorific value at 7.5% adhesive were below the standard. According to the ITEBE standard, only density did not meet the requirement, while other parameters complied, with seven treatment combinations failing to achieve the calorific value threshold. The analysis of variance indicated that adhesive proportion had no effect on moisture content. The stem part was shown to affect density, while the interaction of factors influenced ash content and calorific value. Both stem part and adhesive proportion affected fixed carbon and volatile matter. The best pellet quality was obtained from the stem part with 10% adhesive. Further studies are required to enhance density, particularly through hot pressing techniques